Analisis Efektivitas, Efisiensi, Dan Kontribusi Penerimaan Pajak Reklame Terhadap Pad Kota Surakarta Tahun 2017 – 2021 (Studi Kasus Pada Badan Pendapatan Pengelolaan Keuangan Dan Aset Kota Surakarta) - Stefanus Jati Laksono; Nursiam (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study was to determine and analyze the effectiveness level, efficiency level, and contribution level of billboard tax revenue to Surakarta City's local revenue (PAD) in 2017-2021. This type of research is descriptive research with a quantitative approach. The analysis method used is quantitative descriptive analysis, namely, data analysis techniques that use numbers to draw conclusions from measurable events, in this case by comparing the calculation results of the research. Data collection techniques are literature study techniques and field research with the research subject of the Surakarta City Financial and Asset Management Revenue Agency (BPPKAD). The results showed that, the effectiveness level of billboard tax revenue in the category is very effective with an average of 107%. The efficiency level of billboard tax revenue is in the very efficient category with an average of 4.73%. The contribution rate of billboard tax revenue is in the very poor category with an average of 2.15%. The obstacles faced in collecting billboard tax are, namely, lack of taxpayer obedience, many illegal billboards, lack of human resources in tax collection, less than optimal collection of billboard tax receivables. The solutions carried out by the government in dealing with obstacles are, adding tax collection human resources from third parties, direct socialization to taxpayers, giving strict sanctions, and giving prizes to obedient taxpayers.